2022
DOI: 10.1186/s13014-022-02017-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of locoregional extension of unilateral nasopharyngeal carcinoma and suggestions for clinical target volume delineation

Abstract: Background To summarize the characteristics of local invasion and distribution of metastatic lymph nodes in unilateral nasopharyngeal carcinoma (NPC) by magnetic resonance imaging (MRI) to provide references for the optimization of clinical target volume. Methods MRI and clinical data of 176 cases of unilateral NPC admitted to the Hunan Cancer Hospital from January 2019 to December 2019 were collected. Unilateral NPC was defined as a lesion confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Sanford et al [ 19 ] advocated covering the Meckel’s cave and cavernous sinus ipsilaterally for lateralized tumors. Wu et al [ 21 ] recently characterized the locoregional extension patterns of unilateral NPC and demonstrated that contralateral skull base was not invaded in this case. In accordance with these, our study showed all cases relapsed at unilateral cavernous sinus, most cases at the same side of the primary tumor.…”
Section: Discussionmentioning
confidence: 76%
“…Sanford et al [ 19 ] advocated covering the Meckel’s cave and cavernous sinus ipsilaterally for lateralized tumors. Wu et al [ 21 ] recently characterized the locoregional extension patterns of unilateral NPC and demonstrated that contralateral skull base was not invaded in this case. In accordance with these, our study showed all cases relapsed at unilateral cavernous sinus, most cases at the same side of the primary tumor.…”
Section: Discussionmentioning
confidence: 76%
“…Tomita et al 16 reported a bilateral RLN metastasis rate of 18% in 76 patients with unilateral NPC on the patterns of RLN metastasis in newly diagnosed NPC patients. Wu et al 18 reported a bilateral RLN metastasis rate of 56.3% in 176 patients. In our study, the bilateral lymph node metastasis rate was 57.9%, indicating that unilateral NPC also carries a higher risk of bilateral RLN metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…reported a bilateral RLN metastasis rate of 18% in 76 patients with unilateral NPC on the patterns of RLN metastasis in newly diagnosed NPC patients. Wu et al 18 . reported a bilateral RLN metastasis rate of 56.3% in 176 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An endoscopic biopsy study has revealed a low incidence of occult microscopic disease in the contralateral nasopharyngeal mucosa in unilateral NPC which did not cross the midline [ 8 ]. The risk of skipped discontinuous invasion to the contralateral parapharyngeal space and skull base is also exceedingly low in unilateral NPC, making unilateral irradiation an attractive option to reduce radiation side effects, such as trismus and xerostomia [ 10 ].…”
Section: Target Delineationmentioning
confidence: 99%